What is the safest mode of delivery for extremely preterm cephalic/non-cephalic twin pairs? A systematic review and meta-analyses - Catherine Dagenais; Anne-Mary; Marinela Grabovac; Amit Mukerji; Sarah D. McDonald (BMC, 2017)
Abstract Background Given the controversy around mode of delivery, our objective was to assess the evidence regarding the safest mode of delivery for actively resuscitated extremely preterm cephalic/non-cephalic twin pairs before 28 weeks of gestation. Methods We searched Cochrane CENTRAL, MEDLINE, EMBASE and  http://clinicaltrials.gov from January 1994 to January 2017. Two reviewers independently screened titles, abstracts and full text articles, extracted data and assessed risk of bias. We included randomized controlled trials and observational studies. Our primary outcome was a composite of neonatal death (<28 days of life) and severe brain injury in survivors (intraventricular hemorrhage grade ≥ 3 or periventricular leukomalacia). We performed random-effects meta-analyses, generating odds ratios with 95% confidence intervals for the first and second twin separately, and for both twins together. We assessed the risk of bias using a modified Newcastle Ottawa Scale (NOS) for observational studies and used Grading of Recommendations Assessment, Development and Evaluation approach (GRADE). Results Our search generated 2695 articles, and after duplicate removal, we screened 2051 titles and abstracts, selecting 113 articles for full-text review. We contacted 36 authors, and ultimately, three observational studies met our inclusion criteria. In cephalic/non-cephalic twin pairs delivered by caesarean section compared to vaginal birth at 24+0-27+6 weeks the odds ratio for our composite outcome of neonatal death and severe brain injury for the cephalic first twin was 0.35 (95% CI 0.00-92.61, two studies, I2 = 76%), 1.69 for the non-cephalic second twin (95% CI 0.04-72.81, two studies, I2 = 55%) and 0.83 for both twins (95% CI 0.05-13.43, two studies, I2 = 56%). According to the modified Newcastle Ottawa Scale we assessed individual study quality as being at high risk of bias and according to GRADE the overall evidence for our primary outcomes was very low. Conclusion Our systematic review on the safest mode of delivery for extremely preterm cephalic/non-cephalic twin pairs found very limited existing evidence, without significant differences in neonatal death and severe brain injury by mode of delivery.